2011
DOI: 10.1016/j.otsr.2010.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Non-simultaneous bilateral hip fracture: Epidemiologic study of 241 hip fractures

Abstract: IV, retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
27
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 27 publications
7
27
4
1
Order By: Relevance
“…We found that the characteristics of our cohort were similar to those reported in the literature so far: the majority of patients with hip fracture were female (85%); almost half of the second, contralateral hip fractures occurred within two years of the first hip fracture; and the anatomical classification of contralateral fractures was identical to the primary fracture in more than two thirds of patients [10,29,30] [12,18] [18,30,31]. Approximately 8% of all hip fracture patients in our study sustained a second hip fracture, this is comparable to incidence rates found in the literature [7,8,10].…”
Section: Discussionsupporting
confidence: 81%
“…We found that the characteristics of our cohort were similar to those reported in the literature so far: the majority of patients with hip fracture were female (85%); almost half of the second, contralateral hip fractures occurred within two years of the first hip fracture; and the anatomical classification of contralateral fractures was identical to the primary fracture in more than two thirds of patients [10,29,30] [12,18] [18,30,31]. Approximately 8% of all hip fracture patients in our study sustained a second hip fracture, this is comparable to incidence rates found in the literature [7,8,10].…”
Section: Discussionsupporting
confidence: 81%
“…Because of the variety and complexity of osteoporotic fractures, the precise determination of risk factors for each osteoporotic fracture might be virtually impossible (20). However, some osteoporosis patients might be susceptible to neck fractures and some to trochanteric fractures, based on the fact that contralateral hip fractures are reportedly of the same anatomical type as the primary fractures (21). Therefore, determination of characteristic risk factors for each fracture might lead to more effective prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Les pathologies chroniques seraient associées à la présence d'une MPE. La FEPF prédirait un risque de 10 % de survenue d'une FEPF controlatérale à 5 ans [29,30] et 5 % des patients recevraient un traitement anti-ostéoporotique après une première FEPF [29] pour 2 % dans notre étude. Notre score est en moyenne plus élevé car, d'après le guide de cotation, les fractures osseuses constituent une co-morbidité sévère pour 100 % des patients.…”
Section: Discussionunclassified